2016
DOI: 10.1016/j.apenergy.2016.07.115
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic characterization of isooctane spray in the near field under flash boiling condition

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…A similar spray collapse was reported by Xu et al [13]. They investigated the effect of flash boiling on gasoline, ethanol, methanol and n-hexane sprays formed at different injection pressures (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). They focused on the flash-boiling effects in terms of three spray-formation regimes: subcooled, transitional and flare flash-boiling.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…A similar spray collapse was reported by Xu et al [13]. They investigated the effect of flash boiling on gasoline, ethanol, methanol and n-hexane sprays formed at different injection pressures (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). They focused on the flash-boiling effects in terms of three spray-formation regimes: subcooled, transitional and flare flash-boiling.…”
Section: Introductionsupporting
confidence: 57%
“…According to the study of Vanderwege and Hochgreb [3], for the same liquid, a superheat degree of about 20 K is needed to detect noticeable changes in the spray structure. More recently, Wang et al [10] studied the influence of injection pressure on iso-octane sprays formed under flash-boiling conditions by a single-hole injector. They reported that the higher injection pressure led to a narrower spray angle.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [15] studied the near nozzle single hole spray pattern under flash boiling conditions and observed increased cone angle and spray area when flash boiling occurs. Wu et al [16] studied 1-hole, 2-holes, and 6-holes sprays at near nozzle region from flare flash to sub-cooled conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies using single hole injector showed that under flash boiling conditions, liquid penetration length reduces compared to normal fuel temperature cases. [34][35][36][37] However, spray characteristics are entirely different for multi-hole GDI injector. Chamber pressure and fuel temperature are generally responsible for fuel flashing.…”
Section: Introductionmentioning
confidence: 99%